1-2-sinf o‗quvchilarining jismoniy tayyorgarligini «salomatlik» testlari yordamida baholash (SCIENCE and SOCIETY, 2023)
The relationship between sensitive periods and motor skills was studied in 1-2 graders, and the role of adaptability in the development of the organism was shown. During the annual educational cycle, a pedagogical experiment was conducted using "Health" health tests to monitor the dynamics of movement qualities in children of primary school age.